Dynamics of Somatic and Comorbid Mental Disorders (Distress, Anxiety, Somatisation and Depression) in Patients with Irritable Bowel Syndrome during Therapy with Alimemazine: Results of an Non-Interventional Observational Programme (“Terra”) - V. T. Ivashkin; O. Z. Okhlobystina; M. V. Mayevskaya; O. S. Shifrin; Z. A. Mamieva; Yu. E. Azimova (Российский журнал гастроэнтерологии, гепатологии, колопроктологии)
Aim. This study is aimed at investigating the efficacy and safety of alimemazine (Teraligen®) therapy in patients with irritable bowel syndrome (IBS) associated with comorbid mental disorders (distress, anxiety, somatisation and depression).Materials and methods. During an open-label, non-comparative and non-interventional study, 60 patients diagnosed with the K58 (K 58.0, K58.9) irritable bowel syndrome were observed (12 men and 48 women, average age 39.6 ± 11.1 years) and treated with Teraligen® (alimemazine) with a gradual dose increase from 2.5 to 15 mg per day against the background of the standard symptomatic treatment used for such states. The observational study lasted for 4 weeks. The Four-Dimensional Symptom Questionnaire (4DSQ) was used to assess the dynamics and effectiveness of the treatment in terms of the patients’ mental state, while the “7 symptoms per 7 days” (“7 × 7”) questionnaire was used to assess the dynamics of IBS symptoms and concomitant functional dyspepsia (FD). Both questionnaires were offered to the patients three times: before the start of the treatment and following 2 and 4 weeks of the therapy.Results. Teraligen therapy along with the standard symptomatic treatment has shown a significant positive dynamics of the patients’ state due to the reduction of such symptoms, as pain and burning sensation in the epigastrium, postprandial fullness, early satiety, abdominal pain before defecation, abdominal distension, impaired frequency and quality of defecation. This is confirmed by a reliable and consistent decrease in the total scores of the “7 × 7” questionnaire, with the scores changing from 19.7 ± 7.1 to 11.6 ± 5.9 and 7.3 ± 5.6 before treatment, on the 14th day (p <0.0001) and on the 28th day of therapy (p <0.0001), respectively. The number of patients reporting no symptoms increased by 18.3 %, indicating a complete reduction of severe disorders. The proportion of patients with the minimal or mild severity of complaints increased by 36.7 % and 8.2 % (from 3.3 % to 40.0 % and from 11.8 % to 20.0 %), respectively. In addition, alimemazine treatment contributed to a statistically significant positive dynamics of the patients’ psychoemotional state. The average level of distress decreased from 14.9 ± 10.0 to 7.5 ± 6.2 (14th day) and to 4.4 ± 5.8 scores (28th day). The number of patients reporting no distress symptoms increased by 49.4 %, reaching 91.1 % (n = 51) on the 28th day of treatment. The mean level of depression decreased from 1.7 ± 2.7 to 0.5 ± 1.2 (14th day) and to 0.5 ± 1.6 (28th day), while the proportion of patients without depression increased by 17.9 % and reached 94.6 % (n = 53). The anxiety level was reduced from 6.0 ± 6.3 to 2.9 ± 4.3 (14th day) and to 1.5 ± 3.8 scores (28th day), and the proportion of patients without anxiety increased by 21.4 % reaching 96.4 % (n = 54) (28th day). The level of somatisation decreased from 13.5 ± 7.3 to 8.7 ± 5.6 (14th day) and to 5.1 ± 4.4 scores (28th day), and the proportion of patients without somatisation increased by 52.9 % and comprised 92.9 % (n = 52) (28th day) (according to the 4DSQ). Most of the patients tolerated alimemazine at a dose of 15 mg/day. In 15 patients, minor adverse reactions were observed; however, no cases of pronounced and severe side effects were recorded. In 4 patients, the treatment was cancelled due to increased drowsiness.Conclusion. It is shown that the application of alimemazine (Teraligen®) in patients with IBS and concomitant FD associated with comorbid mental disorders (distress, anxiety, somatisation and depression) reduces gastroenterological (somatic) and mental (affective, somatoform) symptoms, improves the patients’ state of health, thus being confirmed as effective and safe.